2022
DOI: 10.1007/s10980-022-01443-7
|View full text |Cite
|
Sign up to set email alerts
|

Buddhist monasteries facilitated landscape conservation on the Qinghai-Tibetan Plateau

Abstract: Context The Sanjiangyuan region of the Qinghai-Tibetan Plateau—also known as the “Three Rivers’ Headwaters”—is the origin of the Yellow, Yangtze, and Mekong Rivers and therefore the key water source for hundreds of millions of downstream residents. Protecting this region’s ecosystems is a key priority for sustainable development in China and Asia. An important social dimension of Sanjiangyuan is the long-established and widespread presence of Tibetan Buddhism, particularly as manifested in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Our hypothesis was based on the protective effect of monasteries on the surrounding habitat as well as the provision of food resources to local wildlife populations. Previous research has shown that the average area of habitat protected by a monastery is typically within 5 km (Cui et al., 2022), and the food provided by monasteries is limited to wildlife within the immediate surrounding area. Therefore, it is unlikely that a single monastery would have a significant correlation with bird diversity (Kühnert et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our hypothesis was based on the protective effect of monasteries on the surrounding habitat as well as the provision of food resources to local wildlife populations. Previous research has shown that the average area of habitat protected by a monastery is typically within 5 km (Cui et al., 2022), and the food provided by monasteries is limited to wildlife within the immediate surrounding area. Therefore, it is unlikely that a single monastery would have a significant correlation with bird diversity (Kühnert et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The human footprint index data were obtained from the human footprint data set of the Qinghai–Tibet Plateau from 2017, which used six types of spatial data to represent human activities, including population density, land use, grazing density, night lighting, railway and road (Duan & Luo, 2019). Additionally, we chose the ratio of forest habitat, grassland habitats and open space and human footprint index under three different scales (1 km radius, 3 km radius and 5 km radius) from the centre of monasteries/non‐monastery sites/celestial burial grounds, considering that monasteries are known to have an influence on the immediate adjacent land cover up to a distance of 5 km (Cui et al., 2022). We also selected additional landscape factors that could be correlated with bird community composition and abundance, such as the distance to the nearest water and altitude.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of traditional villages on the surrounding land can be measured by establishing a buffer zone [42]. In order to further explore the impact of ethnic villages on various indicators of sustainable development, according to the area and precision of the study area, we set up two buffer zones every 2km with ethnic villages as the center using the MultipleRingBuffer tool and r as the radius (r1 = 2 km, r2 = 4 km) in ArcGIS10.4 software, calculated and compared the values of landscape index, ESV and resistance in the buffer zone from 1995 to 2020 [43][44][45].…”
Section: Buffer Establishmentmentioning
confidence: 99%